The Effect of Web Design and Price on Buying Interest in Shopee E-Commerce - Margaretha Sartien Kabanga; Hairil Nurdin; Benaya Haposan Samosir (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
This study aims to analyze the influence of Web Design and Price variables on Purchase Intention on the Shopee e-commerce platform in Kupang City using a multiple linear regression model. The analysis results indicate that the regression model meets the requirements, showing an initial Purchase Intention value before considering the independent variables. The regression coefficients demonstrate that improvements in Web Design and Price positively impact Purchase Intention. The F-test confirms that both variables significantly influence Purchase Intention, with the calculated values exceeding the required thresholds. The t-test further reveals that both Web Design and Price have a significant individual impact. The coefficient of determination indicates that the model explains a considerable portion of the variability in Purchase Intention, although a substantial portion remains unexplained, suggesting the potential influence of other factors beyond the scope of this study.